1999
DOI: 10.1128/mcb.19.11.7577
|View full text |Cite
|
Sign up to set email alerts
|

PBX and MEIS as Non-DNA-Binding Partners in Trimeric Complexes with HOX Proteins

Abstract: These related genes fall into 13 paralogous groups. The products of groups 1 to 8 are more similar to the fly HOX protein Antennapedia (ANTP class), while 9 to 13 are related to the fly Abdominal-B (ABD-B class).Hox gene products function as sequence-specific DNA-binding transcription factors, as evidenced by their ability to regulate natural and artificial promoters in cell culture (18,48,49,53,61,63) and in the animal embryo (3,12,21,33,45,47,51,64).Homeodomain-DNA interactions are facilitated through residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(173 citation statements)
references
References 64 publications
4
167
1
Order By: Relevance
“…However, by interacting with other transcription factors they can diversify their binding targets. Interacting partners for HOX proteins can be other homeodomain-containing factors (32)(33)(34)(35), and they synergistically govern the expression of downstream target genes. We noticed that nonclustered homeobox genes are also frequent targets of hypermethylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, by interacting with other transcription factors they can diversify their binding targets. Interacting partners for HOX proteins can be other homeodomain-containing factors (32)(33)(34)(35), and they synergistically govern the expression of downstream target genes. We noticed that nonclustered homeobox genes are also frequent targets of hypermethylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has shown that the Meis protein and other homeobox-containing proteins, such as Pbx and Hox family proteins form trimeric complexes in vivo and augment the a nity and speci®city of DNA binding (Chang et al, 1996(Chang et al, , 1997Ryoo et al, 1999;Lu et al, 1995;Neuteboom et al, 1995;Phelan et al, 1995;Berthelsen et al, 1998;Swift et al, 1998;Jacobs et al, 1999;Shanmugam et al, 1999;Shen et al, 1999). Since Xmeis1a did show a weak ability to induce XGli-3, it was a possibility that the two alternatively spliced forms of Xmeis1 (Xmeis1a and Xmeis1b) may cooperate with each other to induce XZic gene expression.…”
Section: Xmeis1a and Xmeis1b Do Not Show Cooperative Activitymentioning
confidence: 99%
“…In mammals, while the majority of Hox proteins interact with Pbx (Hox paralogs 1 ± 10) (Chang et al, 1995;Neuteboom et al, 1995;Phelan et al, 1995), only the group 9 and 10 Abd-B class Hox proteins complex with Meis (Shen et al, 1997). Meis, Pbx, and Hox family members have also been reported to form trimeric complexes in vivo (Berthelsen et al, 1998;Swift et al, 1998;Jacobs et al, 1999;Shanmugam et al, 1999;Shen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The MSCV-HAMeis1(N51S)-YFP (Meis1(N51S) virus) was constructed by replacing the HA-Meis1 portion of the Meis1 virus by a HAMeis1 cDNA containing an asparagine to serine substitution at position 51 of the homeodomain (kindly provided by Dr Mark Featherstone, McGill University, Montreal, Quebec). 19 …”
Section: Retroviral Vectors and Engineering Of Novel Nup98-hox Fusionmentioning
confidence: 99%
“…This was directly tested by transducing the ND13 and NA10 lines with a Meis1 mutant, Meis1(N51S), previously shown to be incapable of binding to DNA, due to an asparagines-to-serine substitution in the residue 51 of its homeodomain. 19 The subclones ND13-2.15 and NA10-3.4 lines were first used to Southern blot analysis of genomic DNA from the bm of moribund mice confirmed the presence of NUP98-Hox and Meis1 proviruses (total time spent in culture prior to injection also shown). Genomic DNA was digested with XbaI, which cuts in both retroviral LTRs, and the eGFP cDNA was used as proviral probe.…”
Section: Meis1 Can Convert Nup-hox Lines Into Aml-inducing Cells Withmentioning
confidence: 99%